Quantification of eight water soluble vitamins in Sutherlandia frutescens species from Botswana using a validated reversed phase HPLC method. Issue 6 (10th May 2019) - Abibu, Moshood A.; Takuwa, David T.; Sichilongo, Kwenga
Abstract: A simple and rapid‐reversed phase high‐performance liquid chromatography method for the separation and quantification of water‐soluble vitamins; B1, B2, B3, B4, B6, B9, B12 and C from Sutherlandia frutescens (a traditionally used medicinal plant found in Botswana), is presented. Vitamins were extracted using ultrasonic assisted extraction while clean‐up was done by solid‐phase extraction with silica‐based C‐18 cartridges. Eight vitamins were separated and identified using an Agilent 1260 Infinity HPLC system fitted with a diode array detector. Two different types of silica‐based bonded C18 columns of equal length and internal diameter were compared for their separation efficiencies using a methanol/formic acid mobile phase system at flow rates of 0.5 and 1.0 mL/min on a gradient elution programme. The separation of eight water‐soluble vitamins was achieved in 12 min at 266 nm. Analytical performance charactristics were evaluated for percent recovery, precision as percent relative standard deviation, limits of detection, limits of quantification and linearity for each vitamin. The method developed herein was applied to determine some water soluble vitamins in a Sutherlandia frutescens plant from Botswana.